Autoimmune dysautonomia in women with silicone breast implants. Issue 120 (June 2021) - Halpert, Gilad; Watad, Abdulla; Tsur, Avishai M.; Dotan, Arad; Quiros-Lim, Hector Enrique; Heidecke, Harald; Gilburd, Boris; Haik, Josef; Levy, Yair; Blank, Miri; Amital, Howard; Shoenfeld, Yehuda
Abstract: Importance and objectives: There is unmet medical need to understand the pathogenic mechanism of the panoply of clinical manifestations associated with silicone breast implants (SBIs) such as severe fatigue, widespread pain, palpitations, dry mouth and eyes, depression, hearing loss etc. We aimed to determine whether autoantibodies against the autonomic nervous system receptors can explain the enigmatic and subjective clinical manifestation reported by women with SBIs. Results: Circulating level of autoantibodies against G protein-coupled receptors (GPCRs) of the autonomic nervous system (adrenergic, muscarinic, endothelin and angiotensin receptors) have been evaluated in symptomatic women with SBIs using an ELISA method. These women with SBIs addressed our clinic due to various subjective and autonomic-related manifestations such as chronic severe fatigue, cognitive impairment, widespread pain, memory loss, sleep disorders, palpitations, depression, hearing abnormalities etc. We report for the first time, a significant reduction in the sera level of anti-β1 adrenergic receptor (p < 0.001), anti-angiotensin II type 1 receptor (p < 0.001) and anti-endothelin receptor type A (p = 0.001) autoantibodies in women with SBIs (n = 93) as compared with aged matched healthy women (n = 36). Importantly, anti-β1 adrenergic receptor autoantibody was found to significantly correlate with autonomic-related manifestations such as: sleep disorders and depression in women with SBIs. Conclusions: Chronic immune stimulation by silicone material may lead to an autoimmune dysautonomia in a subgroup of potentially genetically susceptible women with SBIs. The appearance of autoantibodies against GPCRs of the autonomic nervous system serve as an explanation for the subjective autonomic-related manifestations reported in women with SBIs. Highlights: We report autoimmune dysautonomia in women with silicone breast implants. We found imbalance in circulating autoantibodies against autonomic receptors. Anti-β1 adrenergic receptor antibody was reduced in women with silicone implants. Anti-β1AR autoantibody correlates with autonomic-related clinical manifestations. Antibodies against autonomic autoantigens may explain autonomic-related symptoms.